Combination of conventional immunohistochemistry and qRT-PCR to detect ALK rearrangement - Shan, Ling (BioMed Central, 2014)
BACKGROUND: Compared with FISH and qRT-PCR analyses, immunohistochemistry (IHC) is the preferred screening test in most pathology practices for ALK-rearrangement detection. With 100% sensitivity and 98% specificity, the VENTANA ALK (D5F3) IHC assay has been approved in the EU and some Asian countries for ALK-rearrangement detection. However, an automated Ventana IHC platform is not available in most pathology labs. In this study, we evaluated the applicability of conventional IHC with D5F3 antibody in routine pathological practice and proposed detection methods and procedures that ensure that patients with ALK+ are not missed. METHODS: FISH and IHC analyses were performed on 297 lung adenocarcinoma cases. VENTANA IHC and qRT-PCR assay were applied to evaluate ALK-fusion status in the discordant cases of FISH and IHC. The association of ALK+ with clinicopathological characteristics was statistically analyzed. RESULTS: IHC had 100% sensitivity and 81.8% specificity for detecting ALK+. Eight ALK-expressed cases were ALK-, five of which had ALK fusion detected by qRT-PCR analysis. Three of these five cases showed ALK expression using VENTANA IHC assay. ALK+ was associated with younger age and lymph node metastasis in this Chinese lung adenocarcinoma patient cohort. CONCLUSIONS: The advantages of low cost and 100% sensitivity allow conventional IHC to serve as a robust diagnostic tool for screening patients with ALK+, especially in pathology labs without a VENTANA IHC platform. For cases in which ALK is weakly expressed, qRT-PCR is necessary as a diagnostic test for ALK-fusion detection. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2269448351088278.